Hemoglobin Messenger RNA from Human Bone Marrow ISOLATION AND TRANSLATION IN HOMOZYGOUS AND HETEROZYGOUS β-THALASSEMIA - Nienhuis, A. W. (1973)
A method for isolating human hemoglobin messenger RNA (mRNA) from bone marrow cells was developed to investigate the molecular basis for the defect in globin synthesis in beta thalassemia. Active mRNA was isolated from the bone marrow cells and peripheral reticulocytes of patients with homozygous beta thalassemia, heterozygous beta thalassemia, sickle cell trait, double heterozygosity for beta thalassemia and sickle cell trait, as well as from a patient with normal hemoglobin synthesis but with an elevated reticulocyte count secondary to hereditary spherocytosis. The mRNA was prepared for assay in an mRNA-dependent rabbit reticulocyte cell-free system and the amount of alpha and beta globin chains synthesized was determined by carboxymethylcellulose column chromatography. The relative synthesis of alpha to beta chains in response to normal hemoglobin mRNA was found to be a function of the amount of mRNA added to the assay system: increasing the amount of mRNA led to a decrease in the alpha-to-beta-chain synthetic ratio. Therefore, assays were carried out at limiting concentrations of mRNA. The molecular defect in homozygous beta thalassemia was shown to be carried in the mRNA of bone marrow cells as well as in the mRNA from peripheral reticulocytes, because much less beta than alpha globin was produced in the cell-free system in response to mRNA from either type of cell. In patients doubly heterozygous for beta thalassemia and sickle cell trait, little or no synthesis of beta(A) globin occurred in the bone marrow cells or the peripheral reticulocytes. The alpha to beta(S) synthetic ratio of the intact bone marrow cells was approximately 1, while the same ratio in the peripheral reticulocytes was between 1.5 and 2. The virtual absence of translatable beta globin mRNA in the mRNA prepared from the cells of these doubly heterozygous patients further demonstrates that the molecular defect produced by the beta thalassemia gene is in the beta globin mRNA.